Microgrid optimal control using demand response programs - Akhgarzarandy, Farshad (Ciência e Natura, 2015)
This study, in order to address the issue of frequency and voltage regulation in a Microgrid tries. A central demand coupled with a comparative Tphnvrdy method is applied to a small Microgrid. All dynamical models in Simulink software / MATLAB simulation has been. Simulation results show that the proposed method is able to overcome the voltage changes, voltage Microgrid keep it stable.